2011
DOI: 10.1016/j.psychres.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Examining a progressive model of self-stigma and its impact on people with serious mental illness

Abstract: The self-esteem of some people with serious psychiatric disorders may be hurt by internalizing stereotypes about mental illness. A progressive model of self-stigma yields four stages leading to diminished self-esteem and hope: being aware of associated stereotypes, agreeing with them, applying the stereotypes to one's self, and suffering lower self-esteem. We expect to find associations between proximal stages -- awareness and agreement -- to be greater than between more distal stages: awareness and harm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
255
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(281 citation statements)
references
References 23 publications
17
255
0
9
Order By: Relevance
“…This is consistent with data from chronic illness showing that negative stereotypes only affected morale if accepted as applicable to oneself, 84 and some evidently have good insight without self-stigmatization, 78 but these processes explain resistance to change in some patients.…”
Section: Antipsychotic Formulation Long Acting Injectablesupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with data from chronic illness showing that negative stereotypes only affected morale if accepted as applicable to oneself, 84 and some evidently have good insight without self-stigmatization, 78 but these processes explain resistance to change in some patients.…”
Section: Antipsychotic Formulation Long Acting Injectablesupporting
confidence: 89%
“…84 and similar predictive validity. 11 Individuals' adherence fluctuates: one group 12 found 33%-44% were nonadherent sometime in any 6-month period and 53% sometime in the first 2 years, while another 13 found 63% nonadherent for at least a week over a year.…”
Section: What Is the Prevalence And Impact Of Poor Adherence After Fimentioning
confidence: 65%
“…For instance, Corrigan et al 44 tested a model of self-stigma with 85 people with schizophrenia in the United States and found a significant association between stigma and lowered self-esteem, selfefficacy, and hope. Other studies from Western European countries have also confirmed an association between selfstigma and higher rates of hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Internal stigma occurs if the stigmatised individual agrees with the external stigma and applies the negative appraisal to themselves thus internalising the stigma (Corrigan, Rafacz, & Rüsch, 2011).…”
Section: Introductionmentioning
confidence: 99%